Online Learning Implementation Training for Teachers of SDN Bangetayu Kulon - Cahyaningtyas, Andarini Permata; Jupriyanto, Jupriyanto; Yustiana, Sari; Kusumadewi, Rida Fironika (Universitas Pendidikan Ganesha, 2021)
During the pandemic, elementary school teachers have experienced difficulties in implementing a full online learning system because this was their first time to do it. They have not fully mastered various online learning and assessment method, so they mostly used Whatsapp as the main platform. Those problems were also faced by the teachers of SD Bangetayu Kulon. The purpose of this service is to improve the knowledge and skills of teachers towards bold learning. The subjects of this service are elementary school teachers, totaling 8 people. The training was implemented using several methods, such as lecturing, question and answer, and the direct practice method. The data were collected using observation method. The results showed that all teachers have succeeded to create and manage an online class in Edmodo and conducting online assessments by using Kahoot! and Quizizz. After this training, they will be able to conduct a more organized and interesting online learning using various platforms.